Digital Education Game for TK-A Level Students Using Multimedia Development Life Cycle Method - Benawan, Ivan; Nugraheni, Dinar Mutiara Kusumo; Noranita, Beta; Aryotejo, Guruh (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
COVID-19 pandemic has changed human life. One of the impacted sectors is education. Ministry of Education urges students to implement distance learning. No exception with early childhood education or Pendidikan Anak Usia Dini (PAUD). Although distance learning has been widely implemented, PAUD sector has the lowest online learning implementation in Indonesia with 13.2% of total 98.4% of PAUD students implementing distance learning, whereas early age is considered capable of gaining an understanding of digital technology and equipment. One possible step in conducting digital learning in PAUD is through a digital educational game, because game is an important element in PAUD. In this study, a digital educational game was developed for TK-A level students using Scratch 3 with multimedia development life cycle method. After development, the game goes through two stages of testing. Alpha testing in the form of black box testing, and beta testing in the form of usability testing with 94,39% result, confidence testing with 97,8% result, and summative evaluation with 90% result on TK-A students, as well as interviews with PAUD teachers. The test results indicate that the game has been successfully developed and is feasible to be played by TK-A students.